Organizational Changes; Bibliometric Analysis For 2016-2022 - Tri Noviana; Eni Sulistyawati; Pinondang br Sagala; Romiyati (SMARTINDO, 2023)
Purpose - This study aims to determine the changes that are taking place and to analyze Organization Change publication trends regarding the number of articles, the number of citations to a journal, the relevance of affiliation, the most authors, publishers and network clusters.This research is the first step to look at existing research and find research themes related to organizational change Design/methodology/approach - This research uses the Bibliometric analysis method. The data was obtained through searching the Google Scholar (GS) database with the word Organization Change in the category Article title, Abstract, Keywords. Approximately 153 articles were obtained in the initial results with 569 citations (56.9 citations/year) Findings and Discussion – The search results obtained 129 articles, the citation data also changed, with 367 citations and 52.43 citations/year, during the 2016-2022 period. From the results, 129 articles were refined and the citation data also changed to 367 citations and 52.43 citations each year. The results of the study show that the most cited authors are a. J Suwaryo HKK, and its most relevant affiliate is the University of Indonesia. b. Aslami and Rahman are the most authors, ejournal.unsrat.ac.id is the largest publisher c. words that often appear are organization change, change, organization, organizational change, and study. Conclusion - Bibliometric mapping supports the scientific explanation between probability theory and evidence. Research on Organizational Change can be developed more broadly on themes that appear few and have not been widely included in research in the last seven years. Therefore, this research is expected to be a reference for further research